2010
DOI: 10.1073/pnas.0907240107
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effects of combined cathepsin B and cathepsin Z deficiencies on breast cancer progression and metastasis in mice

Abstract: The lysosomal cysteine proteases cathepsin B (Ctsb) and cathepsin Z (Ctsz, also called cathepsin X/P) have been implicated in cancer pathogenesis. Compensation of Ctsb by Ctsz in Ctsb −/− mice has been suggested. To further define the functional interplay of these proteases in the context of cancer, we generated Ctsz null mice, crossed them with Ctsb-deficient mice harboring a transgene for the mammary duct–specific expression of polyoma middle T oncogene (PymT), and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
124
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 50 publications
10
124
2
Order By: Relevance
“…JPM treatment did not significantly affect tumor growth (Fig. 4B), despite the abundant cathepsin activity we observed in tumors, the reduction in PyMT tumorigenesis observed when cathepsins B and Z are deleted (Sevenich et al 2010), and the efficacy of this compound in other tumor models (Joyce et al 2004). We confirmed that JPM inhibits cathepsin activity in the PyMT tumors using the cathepsin ABP DCG04 (P = 0.0016) (Supplemental Fig.…”
Section: Cathepsin Inhibition Sensitizes Mammary Tumors To Chemotherapysupporting
confidence: 70%
“…JPM treatment did not significantly affect tumor growth (Fig. 4B), despite the abundant cathepsin activity we observed in tumors, the reduction in PyMT tumorigenesis observed when cathepsins B and Z are deleted (Sevenich et al 2010), and the efficacy of this compound in other tumor models (Joyce et al 2004). We confirmed that JPM inhibits cathepsin activity in the PyMT tumors using the cathepsin ABP DCG04 (P = 0.0016) (Supplemental Fig.…”
Section: Cathepsin Inhibition Sensitizes Mammary Tumors To Chemotherapysupporting
confidence: 70%
“…81 Our group and others have identified critical roles for cathepsins in tumor growth, angiogenesis, invasion and metastasis using both genetic and pharmacological strategies in mouse models of cancer. [82][83][84][85][86][87] For example, during sequential stages of tumor development in the RIP1-Tag2 (RT2) model of pancreatic islet carcinogenesis, 88 we found that expression of a subset of cathepsins (B, C, H, L, S, X/Z) progressively increased. 82 Moreover, most of these cathepsins, except cathepsin L, were provided predominantly by infiltrating TAMs in different tumor microenvironments.…”
Section: Il-4 Induces Cysteine Cathepsin Activity In Tamsmentioning
confidence: 99%
“…The generation and characterization of RT2 and CtsZ À/À mice (mutant Ctsz allele, referred to here as CtsZ) have been previously reported (Hanahan 1985;Sevenich et al 2010). CtsZ heterozygous mice were backcrossed into the C57BL/6 background for nine generations before crossing to RT2 mice.…”
Section: Mouse Strainsmentioning
confidence: 99%
“…We next sought to determine the functional contribution of CtsZ to tumor formation and progression by crossing CtsZ À/À mice (Sevenich et al 2010) into the RT2 background. We first confirmed that CtsZ mRNA expression was indeed absent in the CtsZ À/À RT2 tumors and that expression of other cathepsin family members (CtsB, CtsH, CtsL, and CtsS) did not change between CtsZ À/À and wild-type RT2 tumors (Supplemental Fig.…”
mentioning
confidence: 99%